Business and Emerging Technologies - Baffour, George (Business Expert Press, 2021)
Business and Emerging Technologies is an extensive but straight-to-the-point guide designed to get business students and professionals up to speed with an electrifying range of emergent technologies and concepts in the shortest possible time. Readers will benefit from fluid, well-researched reviews of technologies like artificial intelligence, blockchain, cryptocurrencies, quantum computing, augmented reality, 3D printing, and nanotechnology, and will acquire the factual contexts needed to make insightful decisions as these technologies slowly, but surely, pop up in their occupational nexuses.